Estudo comparativo sobre a influência das agenesias dentárias no padrão cefalométrico - Costa, Luciana Ellen Dantas (2010)
This study aimed to ascertain the influence of dental agenesis in cephalometric pattern in patients residing in the city of João Pessoa / PB, in the year 2009. The sample consisted of 52 patients with congenital absence of one or more teeth (excluding third molars) of both sexes in mixed dentition (group 1, n = 29 patients, aged 8 to 12 years, mean 9.93 ± 1.43 years) and permanent dentition (group 2, n = 23 patients, aged 13 to 18 years, mean 14.63 ± 1.82 years). The data collection covered the diagnosis of tooth agenesis by observing panoramic radiographs and clinical records, and getting in cephalometric lateral radiographs. Were taken twenty cephalometric skeletal and dental nine from cephalograms obtained Cef X ® software (version 2.4). A cross-sectional analysis enabled comparison of the cephalometric pattern of patients with dental agenesis (Groups 1 and 2) the pattern of Brazil, proposed by Martin et al. (1998) - (control group 1 and 2), respectively. Patients with tooth abnormalities were divided into subgroups according to the region of impact (front and back) and hit by absences arch (maxilla and mandible). Data were analyzed using SPSS version 13.0 (Statistical Package for Social Sciences), performing frequency distributions, descriptive measures of achievement for all variables, and statistical tests of comparisons between groups (t test Student's unpaired). The missing teeth more frequently observed in patients in group 1 (mixed dentition), involving the upper lateral incisors (46.3%) and second mandibular premolars (18.5%) patients in group 2 (permanent dentition) the second pre-molars (54.5%) and lateral incisors (18.2%) were most frequently involved. Compared to standard cephalometric Brazilians, patients with dental agenesis in both groups showed significant changes in vertical and horizontal dimension, demonstrated by the reduced length of the jaws, the anterior cranial base and anterior inferior facial height, whereas only in group 2 was observed, mandibular retrusion and significant dental changes associated with tooth agenesis involving the lower arch, were presented. Although it was observed that the tooth abnormalities did not influence the pattern of facial growth in patients in this study, in designing the treatment plan, the orthodontist should consider that the craniofacial dimensions and the relationship interarch, these patients may be changed, in addition to the variations associated with age.